Effect of micro-osteoperforations on the rate of orthodontic tooth movement and expression of biomarkers: a randomized controlled clinical trial - Pradeep RAGHAV; Amit Kumar KHERA; Preeti PREETI; Shalu JAIN; Stuti MOHAN; Anurag TIWARI (Dental Press Editora, 2022)
ABSTRACT Introduction: Micro-osteoperforation is a minimally invasive technique that has been used to accelerate orthodontic tooth movement and reduce treatment duration. However, literature presents conflicting reports about this technique. Objective: To evaluate the effectiveness of micro-osteoperforations on the rate of canine retraction and expression of biomarkers in gingival crevicular fluid (GCF). Methods: This was a randomized clinical trial with split-mouth study design. Thirty adult subjects with age above 18 years (20.32 ± 1.96) who required fixed orthodontic treatment and extraction of maxillary first premolars were enrolled and randomly allocated to either the experimental or control group. Randomization was performed by block randomization method, with a 1:1 allocation ratio. The experimental group received three micro-ostoperforations (MOPs) distal to maxillary canine, using the Lance pilot drill. The retraction of maxillary canine was performed with NiTi coil-spring (150g) in both experimental and control groups. The primary outcome was the evaluation of canine retraction rate, measured on study models from the baseline to 16 weeks of canine retraction. Secondary outcomes were the estimation of alkaline and acid phosphates activity in GCF at 0, 1, 2, 3, and 4 weeks. Results: There was a statistically significant difference in the rate of canine retraction only after the first 4 weeks. Subsequently there was no statistically significant difference from the eighth to the sixteenth weeks between MOPs and control group. There was a statistically significant difference in alkaline and acid phosphates activity in GCF between MOPs and control groups during the initial 4 weeks of canine retraction. Conclusion: Micro-ostoperforation increased the rate of tooth movement only for the first 4 weeks; thereafter, no effect was observed on the rate of canine retraction during 8, 12 and 16 weeks. A marked increase in biomarker activity in the first month was observed.